2015
DOI: 10.1016/j.bbmt.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Positron Emission Tomography with 18F-Fluorodeoxyglucose Integrated with Computed Tomography in the Evaluation of Patients with Multiple Myeloma Undergoing Allogeneic Stem Cell Transplantation

Abstract: Positron emission tomography (PET) integrated with computed tomography (PET/CT) has been reported to be useful for screening myelomatous lesions at diagnosis in patients with multiple myeloma (MM) and for monitoring response to autologous stem cell transplantation (auto-SCT). The aim of the study was to evaluate the prognostic significance of PET/CT in MM patients who received allogeneic stem cell transplantation (allo-SCT). Patients who underwent upfront auto-SCT followed by allo-SCT, either as consolidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 25 publications
3
15
0
1
Order By: Relevance
“…Finally, scarce data on the value of FDG-PET before or after allo-SCT are available but two retrospective studies of heavily pre-treated MM patients showed FDG-PET results prior to and after allo-SCT were strongly associated with the outcome (44, 45).…”
Section: Prognostic Value Of Fdg-pet At Relapse Settingmentioning
confidence: 99%
“…Finally, scarce data on the value of FDG-PET before or after allo-SCT are available but two retrospective studies of heavily pre-treated MM patients showed FDG-PET results prior to and after allo-SCT were strongly associated with the outcome (44, 45).…”
Section: Prognostic Value Of Fdg-pet At Relapse Settingmentioning
confidence: 99%
“…Zamagni et al recruited 192 MM patients and found that number of FLs > 3, SUVmax > 4.2 and EMD were correlated with shorter OS 3. Most studies showed similar result with Zamagni's work; however, they selected different cut-off values for SUVmax 9,27. For these parameters in solid tumors, there are also no recognized standards to define the cut-off value.…”
mentioning
confidence: 98%
“…36 ******Other studies have reported that negative FDG PET/CT scans after ASCT are associated with improved PFS. 62,63 In the context of minimal residual disease assessment, there is a clinical need for more sophisticated instruments to measure residual disease as a potential source of relapse. 64 Minimal residual disease assessment has traditionally been performed on bone marrow biopsy, which is limited as it may not assess actual tumour burden.…”
Section: Bjrmentioning
confidence: 99%